Incidental diagnosis and treatment of posterior urethral valve in a child with osteogenesis imperfecta: a case report - Onwuasoanya, Uzodimma E.; Olatise, Olalekan O.; Epundu, Nonso O.; Igbokwe, Martins C.; Ikeugwoke, Odinaka I.; Adetunbi, Adefola R.; Orji, David O. (International Surgery Journal, 2022)
Posterior urethral valve is the commonest cause of both urinary tract obstruction and chronic renal disease in male children. The patients may present with the complications of the disease such as impaired renal function, urinary tract infection, or anaemia. Reports abound about the association of other congenital defects with posterior urethral valve but few studies have reported the association of this disease with osteogenesis imperfecta. An 8-year-old male on management for osteogenesis imperfecta who presented to our facility following renal function test in keeping with impaired renal function and imaging result in keeping with right renal agenesis and left renal parenchymal disease, these investigations were done as part of work up for surgical treatment of osteogenesis imperfecta. Evaluation revealed posterior urethral valve and he had valvotomy with Mohan’s urethral valvotome with satisfactory improvement in urine stream and renal function after the procedure. Posterior urethral valve can also occur with osteogenesis imperfecta not commonly reported to occur with it. Diagnosis of posterior urethral valve should be ruled out in any male patient with congenital abnormality to avoid missing the diagnosis when present as this can lead to renal failure.